Digital-Based Arabic Language Learning Transformation in Madrasah: A Qualitative Study of Implementation and Challenges - Muhamad Misbahul Munir; Hanik Mahliatussikah; Khairun Nisa (Al-Fakkaar, 2026)
This study explores the implementation and challenges of digitally based Arabic language learning in madrasah. Using a qualitative case study design, data were collected through semi-structured interviews, classroom observations, and document analysis involving Arabic language teachers, students, and school administrators. The data were analyzed using an interactive model consisting of data condensation, data display, and conclusion drawing. The findings indicate that digital media have shifted teachers' and students' perceptions of Arabic language learning from a grammar-oriented approach toward more communicative, contextual, and student-centered practices. However, the implementation remains fragmented due to variations in teachers' digital literacy, limited technological infrastructure, and the absence of institutional policies supporting digital learning. This study contributes to the understanding of digital transformation as a pedagogical-institutional process shaped by the interaction among technology, pedagogical practices, institutional readiness, and organizational culture. The findings provide practical recommendations for strengthening digital learning policies and teacher professional development in madrasah.